A comparative study of the relationship between the recovery of movement and the anatomical alignment in fractures around the elbow - Raj, Manish; Singh Gill, Simrat Pal; Rajput, Ajay Kumar; Singh, Santosh Kumar (International Journal of Research in Orthopaedics, 2019)
Background: The injury around the elbow joint is a common condition in any age group, especially in children as a result of fall, during the course of a child’s normal play. The aim of the present study was to study the relationship between the recovery of movements and the anatomical alignment in fractures around the elbow. Methods: In the present study, 110 cases of fractures around elbow were included. The treatment with conservative or operative procedure depends on the surgeon concerned and his priorities. Sixty-six cases were treated conservatively, and 56 cases required operative intervention. At the time of follow up examination, cases were assessed as to the anatomical and functional point of view according to Flynn’s criteria. We evaluated the reduction as per alignment in anteroposterior axis, lateral axis, and angulation. The patients were followed up for over 24 months. Results: Patients who had good anatomical alignment (grade A) showed 96.87% satisfactory result as compared to the patient who had fair anatomical alignment (91.66%) and poor anatomical alignment (54.54%). Thus in grade A where alignment was up to 76 points, we had satisfactory result in 96.87% patients, where as in grade C where alignment was less than 50 points, the result in 45.5% of patients was poor. Conclusions: Patients who had good anatomical alignment achieved, showed higher recovery of movement compared to the patient who had fair anatomical alignment and poor anatomical alignment.